Bevacizumab with FOLFIRI or XELIRI in the First-line Therapy of Metastatic Colorectal Carcinoma: Results from Czech Observational Registry - Kocakova, Ilona; Melichar, Bohuslav; Kocak, Ivo; Bortlicek, Zbynek; Büchler, Tomas; Dusek, Ladislav; Petruzelka, Luboš; Kohoutek, Milan; Prausová, Jana; Finek, Jindrich; Mohelnikova-Duchonova, Beatrice; Vyzula, Rostislav (Anticancer research, 2015)
AIM: To retrospectively compare the efficacy of two irinotecan-based chemotherapy regimens combined with bevacizumab in first-line therapy of metastatic colorectal cancer (mCRC). PATIENTS AND METHODS: The data of 558 patients with mCRC treated with first-line bevacizumab plus irinotecan-containing regimen were obtained from the national CORECT registry that collects data of all patients with mCRC treated with targeted-agents. The treatment outcomes of patients treated with bevacizumab plus irinotecan, 5-fluorouracil and folinic acid (FOLFIRI) were compared to patients treated with bevacizumab plus irinotecan and capecitabine (XELIRI). RESULTS: Among 4,312 patients with CRC treated with bevacizumab, only 13% (558) received irinotecan-based chemotherapy. No significant differences were observed in terms of progression-free survival and overall survival between FOLFIRI and XELIRI groups. Moreover, the toxicity of both regimens was also comparable. CONCLUSION: This retrospective analysis confirms the comparable activity of FOLFIRI and XELIRI regimens when combined with bevacizumab.
Keywords: nádory jater; Humans; fluoruracil; lidé středního věku; Leucovorin; kamptothecin; Female; Aged; dospělí; protokoly protinádorové kombinované chemoterapie; XELIRI; výsledek terapie; senioři; lidé; humanizované monoklonální protilátky; leukovorin; Liver Neoplasms; přežití bez známek nemoci; FOLFIRI; Adult; Neoplasm Metastasis; Antibodies, Monoclonal, Humanized; metastázy nádorů; bevacizumab; ženské pohlaví; Camptothecin; kolorektální nádory; Male; colorectal cancer; Middle Aged; Retrospective Studies; Treatment Outcome; Antineoplastic Combined Chemotherapy Protocols; Czech Republic; Fluorouracil; Bevacizumab; Disease-Free Survival; retrospektivní studie; Česká republika; mužské pohlaví; Colorectal Neoplasms